ENTREPRENEURIAL PROSPECTS AND CHALLENGES FOR WOMEN AMIDST COVID-19 (International Journal of Food and Nutritional Sciences, 2022)
The global economic structure has been severely impacted by the coronavirus disease 2019 (COVID-19) pandemic, with women-owned businesses bearing the brunt of the damage. This paper aims to encapsulate the gendered support and hindering factors along with the role ofthe state experienced by Chennai based women entrepreneurs in setting up/operating their enterprises amidst thechallenges posed by the coronavirus disease 2019 (COVID-19) pandemic. The study used mixed methods to explore the challenges faced and recovery mechanisms adopted by women entrepreneurs with special reference to the COVID-19 pandemic. There is no readily accessible sampling frame for choosing a sample of women entrepreneurs in Chennai City. Snowballing technique for identifying respondents is used and a sample of 60 women entrepreneurs is selected from Bahawalpur and its surrounded areas for this study. The sample is comprised of women entrepreneurs from a variety of sectors. The research captured data from schedules of these selected women. Data used in this study is primary in nature for which a structured questionnaire is adapted and survey form of women entrepreneurs. This research article adds to the literature on the determinants of problems faced by the women entrepreneurs in Chennai City during COVID-19 pandemic. Very small-scale women entrepreneurs face common as well as gender-based challenges in the context of the market, finance, social capital, family support and awareness in addition to accessing the state’s resources/policies in both their startups and crisis situations, such as the COVID-19 pandemic. The study emphasises the complexities of patriarchy, which stifles women entrepreneurs in all aspects of their lives: family, society, market, and state. As a result, it is recommended that policy be enacted and implemented, as well as additional research on women's entrepreneurship, to focus more deeply on the gender dimension.